PENERAPAN METODE PEMBELAJARAN PREVIEW QUESTION READ REFLECT RECITE AND REVIEW (PQ4R) UNTUK MENINGKATKAN KETEAMPILAN MEMBACA PEMAHAMAN PADA PEMBELAJARAN BAHASA INDONESIA - Kisvanolla, Anugerah; Febriana, Putri Hana; Aprinawati, Iis; Surya, Yeni Fitra; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low reading comprehension skills of students in Indonesian language lessons in grade IV of SD Negeri 007 Pulau Gadang, XIII Koto Kampar District, Kampar Regency. One solution to overcome this problem is to use the PQ4R method. The purpose of this study is to describe the improvement of children's reading comprehension skills into several sentences using the PQ4R method in grade IV students of SD Negeri 007 Pulau Gadang. The research method is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection. The subjects of this study were 10 grade IV students, with 3 male students and 7 female students. Data collection techniques were in the form of tests, observations, and documentation. The results of this study can be concluded that the reading comprehension skills of grade IV students of SD Negeri 007 Pulau Gadang in cycle I were classified as good with an average completion of 75.6%. Furthermore, out of 10 students, 7 students completed, while classical learning was 86%. From the above, it can be concluded that using the Preview Question Read Reflect Recite and Review (PQ4R) method can improve the reading comprehension skills of fourth grade students at SD Negeri 007 Pulau Gadang